The Effect of the Portal System in Achievement Motivation and Cognitive of Fifth Grad Students in Geographic Literary Material (Journal of the College of Education for Women, 2019)
The study aimed to identify the impact of the use of systemic approach in the collection of geographical material and cognitive motivation when fifth grade students of literary, experimental design researcher adopted a partial seizures, and telemetric to two unequal one experimental and the other officer.The sample consisted of fifth grade literary students from secondary (inherent) for Boys in Baghdad (the Republic of Iraq. (By Mjootain, and the number of students of each group (30 students). And has rewarded the two groups, in the variables (chronological age, average scores half-year, degree IQ),Promising researcher himself requirements of research to determine the scientific material and teaching plans and the formulation of behavioral objectives that are consistent with the requirements of the course material.The researcher also relied on the two tests, the first prepared by the researcher was Theselaa test of multiple choice, consisting of (60) and the second paragraph risk trialmeasure adopted researcher Mahmoud (2004) to measure the motivation and cognitive component of the total number (39) paragraph. The total score on the scale ranged between (39-195). The extraction of the virtual display of honesty through tests on a group of experts have been paragraphs analysis by extracting the level of difficulty and discriminatory paragraph of each paragraph. , And was calculating reliability coefficient retail midterm way, the first test and was (0.83) The second test, bringing reliability coefficient (0.81). The data were processed statistically between the control and experimental groups by equation (samples t-test).Have yielded results after analyzing and statistically treated to a difference is statistically significant at the significance level (5 0), and in favor of the experimental group, in the achievement test and measure the cognitive motivationIn light of the findings put the researcher some of the recommendations was the most important use of systemic approach in geographical teaching natural fifth grade literature because of its impact on achievement and stimulate the motivation of knowledge among students and suggested that current research on the outstanding students and identify systemic approach the size of the collection and the development of innovative thinking.